Homo Faber Scapegoated, or Apocalyptic Artificial Intelligence: Rethinking the Technological Singularity Concept from the Synergetic Historicism Position - Irina Gennadievna Mikailova (Journal of Management and Science, 2024)
The article is focused on discussing a new methodological approach to the study on specifics of transferring human beings to the Posthuman cyber society. The approach in question assists in rethinking interconnected problems both of human origins in the Universe and mankind’s digital future. And, besides, such an approach allows to deal with Self-organising interconversions between the poles of the cardinal dual opposition of the Global Noosphere Brain and the Artificial General Intelligence. Herewith such phenomena of digital social life as Global Digitalisation, Digital Immortality, Mindcloning, and Technological Zombification being the constituents of Technological Singularity Concept, are rethought as paving the way for oncoming Posthuman Digital Era. This concept is evidently exemplified by a bifurcation resulting in two alternatives to be chosen by human beings, to wit, either to be undergone Mindcloning and become digitally immortal or being destroyed by powerful intelligent machines.The investigation in question is based on such a progressive methodology as the Law of Self-Organizing Ideals, as well as on the Method of Dual Oppositions. Rethinking interrelationships between the problem of a sense of social history and the meaning-of-life of local societies members which any intelligent machine is devoid of permits to substantiate specific regularities of Self-transforming Homo Faber into Homo Digitalis and Technological Zombies ready to be transferred to Posthuman Cyberspace.